Rent arrears and their implications in public housing - Salleh, Nor Aini; Johari, Noraini; Yusof, Nor’Aini (2008)
The need for housing occurs in tandem with the ongoing urbanisation process. Rapid urban growth has created a factor attracting the rural population toconverge in urban areas due to job opportunities available. This scenario has caused the demand for housing to escalate in line with the migration pattern but unfortunately, the existing supply was unable to fulfil demand for housing. The lack of housing especially for the lower income groups has forced the government to intervene in solving the problem by, amongst others, building public housing for these groups. Housing policies formulated have given ample allowance to the lower income groups either to own such housing or merely to rent.Public housing offers a level of prices and rentals that are much lower than the real market. Unfortunately, this privilege has been abused by the occupants. Their failure to pay rent has caused a lot of pressure to the government namely the housing management to tackle the issue. Rent is a form of revenue to the management to be utilised in carrying out management operations on public housing. If rent collection could not be fully implemented, problems will occur that will not only impact the management but will also have to be borne by the tenants themselves. This paper will discuss in detail the implications of rent arrears from the perspectives of both the management and the residents themselves.